RACIAL STUDY AND CHELIPED FLUCTUATING ASYMMETRY OF BLUE CRABS FROM OLIGOHALINE AND MESOHALINE ESTUARIES OF NIGER DELTA, NIGERIA - UDOH, J.P.; NLEWADIM, A.A. (Nigerian Journal of Fisheries, 2011)
A racial study of Callinectes amnicola was conducted in Imo and Qua Iboe River estuaries, Niger Delta, Nigeria, using morphometry, colour morphotype and cheliped characters to determine variations in its populations. Carapace lengths showed no significant population difference (t-Test, P > 0.05) while total weight and carapace width were greater (P < 0.05) in crabs of the Qua Iboe River estuary. Intersexual and interpopulation variations in body dimensions and condition factor of specimens were not significantly different (t-Test, P > 0.05). Asymmetry of palm depth was significantly different from zero (P < 0.05) reflecting developmental instability from endogenous genetic or exogenous factors resulting from graded distribution and differential growth during development, in favour of male right-handedness within the populations. Chela robustness, chela size and finger size had positive values and exhibited heterochely of 77 - 80% tendency towards right handedness. Three moult stages were encountered, with higher occurrence of green morphotypes (59 – 61%). Significant (P < 0.05) allometry of the carapace length in relation to total weight, carapace width, cheliped palm depth, palm length, finger length and gape was observed with negative correlation with cheliped finger length and fluctuating asymmetry. The exponent b indicated negative allometry in cheliped dimensions in males, females and combined (P < 0.05). The character which affords high discriminatory values between sexes was cheliped palm depth and hence, serves as a secondary sexual character. Interpopulation differences were phenotypic in nature and attributable to salinity differences; hence C. amnicola from Qua Iboe and Imo River estuaries are of the same stock and could be subjected to similar management and conservation regulations.